(untitled) (Castilla. Estudios de Literatura, 2016)
The present article studies the relationship between Heraclitean concepts êthos and daímôn from Classical Antiquity to the first half of the 20th century by analysing the differences between the siren’s myth in The Odyssey and its contemporary readings in Kafka and Joyce. It starts by approaching the relationship Erich Auerbach establishes between both concepts in Homer and Greek Tragedy and opposing them to the modern birth of what Imre Kertész terms “functional man”. It then focuses on Kafka to show the modern lack of communication between character and destiny –the symbol of which is the siren’s silence in Das Schweigen der Sirenen–, as well as a possible answer to the set out nihilism. Regarding Joyce, it studies the chapter “Sirens” from Ulysses to reveal how the modern song’s universal attraction frustrates its listeners’ self-expression.